2019
DOI: 10.1111/jopy.12537
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and actual posttraumatic growth in religiousness and spirituality following disasters

Abstract: ObjectiveReligious/spiritual (R/S) growth is a core domain of posttraumatic growth (PTG). However, research on R/S growth following disasters has over‐relied on retrospective self‐reports of growth. We therefore examined longitudinal change in religiousness/spirituality following two disasters.MethodReligious survivors of Hurricanes Harvey (Study 1) and Irma (Study 2) completed measures of perceived R/S PTG, general religiousness/spirituality (“current standing”‐R/S PTG), and subfacets of religiousness/spiritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
5
18
0
Order By: Relevance
“…In this stratified sample of U.S. adults with chronic diseases (selected to parallel the national, chronically ill population in gender, race/ethnicity, region, and religious affiliation but which was older in age and higher in socioeconomic status), there was little evidence of meaningful change in psychological or spiritual outcomes during the first 3 months of the pandemic. Results align with prior prospective longitudinal studies of natural disasters (Davis et al, 2021) and the COVID-19 pandemic (Luchetti et al, 2020;Velden et al, 2020;Wang et al, 2020), which have found relatively stable trajectories of psychological and spiritual outcomes following disasters.…”
Section: Discussionsupporting
confidence: 87%
“…In this stratified sample of U.S. adults with chronic diseases (selected to parallel the national, chronically ill population in gender, race/ethnicity, region, and religious affiliation but which was older in age and higher in socioeconomic status), there was little evidence of meaningful change in psychological or spiritual outcomes during the first 3 months of the pandemic. Results align with prior prospective longitudinal studies of natural disasters (Davis et al, 2021) and the COVID-19 pandemic (Luchetti et al, 2020;Velden et al, 2020;Wang et al, 2020), which have found relatively stable trajectories of psychological and spiritual outcomes following disasters.…”
Section: Discussionsupporting
confidence: 87%
“…This was consistent with a recent study that revealed a higher level of warmth in parenting to be a possible mechanism facilitating PTG in the child's response to traumatic events ( 25 ). Furthermore, according to the PTG theoretical model ( 6 ), a “good peer relationship” was proposed for trauma intervention. Peer support providing a new cognitive schema or a new perspective on trauma may be conducive to reducing feelings of isolation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The post-traumatic Growth Inventory (PTGI) was used to measure the positive changes of the participants during the COVID-19 epidemic, which was developed by Tedeschi and Calhoun ( 6 ). The scale included 21 items rated on a six-point scale ranging from 0 (no change) to 5 (very great degree of change).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is the value of beliefs about growth following adversity? Davis et al (in press) examined this question with a focus on the perspective of spiritual growth in the wake of two natural disasters. The authors found that participants were typically not accurate in their perceptions of change when compared to their actual assessed change (corroborating past work by Blackie et al, 2017; Frazier et al, 2009; Owenz & Fowers, 2019).…”
mentioning
confidence: 99%